Effects of the Promoting-Children Intervention with Multiple Informants: An Experimental Study - Falcão, Alessandra Pereira [UNESP]; Bolsoni-silva, Alessandra Turini [UNESP] (Universidade de São Francisco, Programa de Pós-Graduação Stricto Sensu em Psicologia, 2024)
Behavior problems are frequent in school-age children; however, few controlled studies have assessed the effects of social skills interventions with this population, especially involving different informants and environments. This study aimed to describe the effects of the Promoting-Children intervention in an experimental group design with children (Experimental Group and Control Group), utilizing various probes and informants, regarding the children’s behaviors before and after the intervention, a follow-up evaluation (social skills, behavior problems, academic performance) and assessment of the teachers and parents’ positive and negative educational practices. Teachers and parents/guardians responded to standardized instruments to measure educational social skills, negative practices, behavior problems, and social skills with various probes. The results demonstrated a reduction in behavior problems and negative practices, as well as an increase in social skills and educational social skills, in both the school and family environments, after the interventions in the Experimental Group, whereas no such changes were observed in the Control Group. This confirms the positive effects of the efficacy and effectiveness of the Promoting-Children intervention.

Problemas de comportamiento son frecuentes en niños en edad escolar y faltan estudios controlados que certifiquen los efectos de intervenciones en habilidades sociales en esa población, especialmente con diferentes informantes y ambientes. El objetivo de la investigación es describir los efectos de la intervención Promueve-Niños en un grupo experimental de niños (Grupo Experimental y Grupo Control), con diferentes sondas e informantes sobre el comportamiento de los niños antes y después de la intervención (habilidades sociales, problemas de comportamiento, rendimiento académico) y prácticas educativas positivas y negativas de sus profesores y sus familiares. Profesores y padres/tutores respondieron a instrumentos estandarizados para medir habilidades sociales educativas, prácticas negativas, problemas de comportamiento y habilidades sociales con diferentes sondas e informantes. Los resultados muestran que hubo una reducción de problemas de comportamiento y de prácticas negativas en los entornos escolar y familiar, así como un aumento de las habilidades sociales y habilidades sociales educativas después de las intervenciones del Grupo Experimental, no ocurriendo en el Grupo Control. Los efectos positivos de la eficacia y de la efectividad del Promueve-Niños son atestiguados.

Problemas de comportamento são frequentes em crianças em idade escolar, mas há poucos estudos controlados para aferir efeitos de intervenções em habilidades sociais com essa população, especialmente com diferentes informantes e ambientes. O objetivo desta pesquisa foi descrever efeitos da intervenção Promove-Crianças, em um delineamento experimental de grupo com crianças (Grupos Experimental e Controle), com diferentes sondas e informantes, sobre os comportamentos das crianças antes e após a intervenção, incluindo avaliação de seguimento (habilidades sociais, problemas de comportamento, desempenho acadêmico) e práticas educativas positivas e negativas de seus professores e familiares. Professores e pais/responsáveis responderam a instrumentos padronizados para mensurar habilidades sociais educativas, práticas negativas, problemas de comportamento e habilidades sociais, nas diferentes sondas. Os resultados demonstraram, nos ambientes escolar e familiar, redução de problemas de comportamento e de práticas negativas e aumento das habilidades sociais e habilidades sociais educativas após as intervenções no Grupo Experimental, não ocorrendo no Grupo Controle. Atesta-se efeitos positivos de eficácia e de efetividade do Promove-Crianças.
Efectos de Promueve-Niños de Múltiples Informantes: Un Estudio Experimental
Efeitos do Promove-Crianças por Múltiplos Informantes: Um Estudo Experimental
Keywords: Behavior Problems; Social Skills; Psychological Intervention; Educational Practices; School; Problemas de comportamento; habilidades sociais; intervenção psicológica; práticas educativas; escola